Pedagogy, ICT skills, and online teaching readiness as factors on digital competency practices among secondary school teachers in Malaysia - Omar, Muhd Khaizer; Mohmad, Ikmal Rizal (Association for Researcher of Skills and Vocational Training, 2023)
COVID-19 has impacted the globe in the most disastrous ways. The widespread COVID-19 has affected the education system from kindergarten to the university level. Most nations responded with alacrity with numerous alternatives to teaching and learning (T&L) strategies. Home-based T&L took place although this belligerent strategy did not fully benefit all students due to their inaccessibility to technology. However, as far as the matter is concerned, home-based T&L was the only option that the ministry could execute. Even if the technology is accessible and usable, the concern is the teachers' abilities and knowledge to integrate ICT in their T&L. Teacher digital competency becomes the forefront issue in this study since risks to students' learning process are disdain. This research explained the relationship between the pedagogical method, the information, and communication technologies (ICT) skills, and online teaching readiness among secondary school teachers in Malaysia. A descriptive and correlational study was employed to determine the level of teacher competency in three aspects: digital pedagogy, ICT skill, and online teaching readiness and the relationship among the aforementioned variables. One hundred and twenty-two teachers from selected high schools in Klang Valley were invited voluntarily to participate in the study. The validated questionnaire was uploaded in the google form and the link was distributed to teachers via email invitation. The results indicated the teacher's digital competency based on pedagogical approaches, ICT, and online teaching was ranked at a high level. It is important to note that there was a strong and positive relationship among the studied variables. The findings projected salient integration of the variables to inspire digital competency practices among teachers successfully.